Review of methods for enhancing interlaminar mechanical properties of fiber-reinforced thermoplastic composites: Interfacial modification, nano-filling and forming technology - Jin, Ziang; Han, Zhenyu; Chang, Cheng; Sun, Shouzheng; Fu, Hongya (Composites science and technology, 2022)
The mechanical properties of thermoplastic composite components in the thickness direction are insufficient to meet the requirements of aerospace and other fields as an alternative to conventional metal structural materials, restricting their use in related structural devices. The methods for improving the interlaminar mechanical properties of thermoplastic composites are reviewed in this work from two perspectives: enhancing the interface properties between fiber and resin and the properties of the interlaminar resin-rich zone. Fiber surface modification means, such as oxidation, plasma, ray irradiation, sizing agent, and carbon nanotubes are detailed introduced. Meanwhile, the effect of different forming technologies and using carbon nanotubes or buckypaper as reinforcement on interlaminar resin-rich zone mechanical properties are discussed. The advantages and disadvantages of each method are then summarized and analyzed. Future research on further improving the interlaminar mechanical properties of thermoplastic composites is prospected. [Display omitted] •The effects of fiber surface modification on the interfacial bonding properties of thermoplastic composites are summarized.•The influence of thermoplastic composite forming technology on the interlaminar resin-rich zone is summarized.•Carbon nanotubes can in situ enhance the properties of the interlaminar resin-rich zone of thermoplastic composites.